Keap1-Nrf2 pathway: a key mechanism in the occurrence and development of cancer - Chen, Feilong; Xiao, Mei; Hu, Shaofan; Wang, Meng (Frontiers in Oncology, 2024)
The Keap1-Nrf2 signalling pathway is a major regulator of the cytoprotective response, participating in endogenous and exogenous stress caused by ROS(reactive oxygen species). Nrf2 is the core of this pathway. we We summarized the literature on Keap1-Nrf2 signaling pathway and summarized the following three aspects: structure, function pathway, cancer and clinical application status. This signalling pathway is similar to a double-edged sword: on the one hand, Nrf2 activity can protect cells from oxidative and electrophilic stress; on the other hand, increasing Nrf2 activity can enhance the survival and proliferation of cancer cells. Notably, oxidative stress is also considered a marker of cancer in humans. Keap1-Nrf2 signaling pathway, as a typical antioxidant stress pathway, is abnormal in a variety of human malignant tumor diseases (such as lung cancer, liver cancer and thyroid cancer). In recent years, research on the Keap1-Nrf2 signalling pathway has become increasingly in-depth and detailed. Therefore, it is of great significance for cancer prevention and treatment to explore the molecular mechanism of the occurrence and development of this pathway.